The prevalence and causes of visual impairment in Tehran: the Tehran Eye Study. Issue 6 (17th May 2004) - Fotouhi, A; Hashemi, H; Mohammad, K; Jalali, K H
Abstract : Aims: To determine the prevalence and causes of visual impairment in Tehran, Iran, through a population based study. Methods: In a population based, cross sectional study, 6497 Tehran citizens were sampled from 160 clusters using a stratified, random, cluster sampling strategy. The eligible people were enumerated through a door to door household survey in the selected clusters and were invited. All participants were transferred to a clinic for an extensive eye examination and interview. Visual impairment was determined using presenting and best corrected visual acuity (low vision: visual acuity of less than 6/18 to 3/60 in the better eye; blindness: visual acuity of less than 3/60 in the better eye). Results: Of those sampled, 4565 (70.3%) people participated in the study. The age and sex standardised prevalences of visual impairment on the basis of best corrected and presenting visual acuity were 1.39% (95% confidence interval (CI), 1.07 to 1.71) and 2.52% (95% CI, 2.07 to 2.97), respectively. 15 people (0.28%; 95% CI, 0.14 to 0.42) were blind with corrected vision while 22 (0.39%; 95% CI, 0.23 to 0.56) were blind with presenting vision. Using the corrected and presenting vision, the prevalence of low visual impairment was 1.11% (95% CI, 0.84 to 1.39) and 2.13% (95% CI, 1.71 to 2.55), respectively. The causes of visual impairment according to the best corrected vision were cataract (36.0%), macular degeneration (20.0%), and amblyopia (10.7%). However, according to the presenting vision, uncorrected refractive errors were the most frequent primary cause (33.6%) and cataract (25.4%), macular degeneration (12.7%), and amblyopia (8.2%) were the other main causes of visual impairment in the study sample. The prevalence of visual impairment was associated with advancing age and lower education. Conclusion: The results indicate that the burden of visual impairment is important and, although easily preventable, uncorrected refractive errors and cataract have a major role as causes of visual impairment in this population. Results also highlight the need for visual impairment prevention programmes, with emphasis on treatment of refractive errors and cataract.